IEEE INFOCOM 2008 - The 27th Conference on Computer Communications 2008
DOI: 10.1109/infocom.2008.284
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Gain of Network Coding in Lossy Wireless Networks

Abstract: Abstract-The capacity gain of network coding has been extensively studied in wired and wireless networks. Recently, it has been shown that network coding improves network reliability by reducing the number of packet retransmissions in lossy networks. However, the extent of the reliability benefit of network coding is not known. This paper quantifies the reliability gain of network coding for reliable multicasting in wireless networks, where network coding is most promising. We define the expected number of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…It has been shown that NC offers exciting benefits in terms of throughput, reliability, cost, and delay in wireless networks [15][16][17][18]. Specifically, the reliability gain of NC was studied recently in [7,19,20]. The work in [19] confirmed that NC could increase the reliability by reducing the number of transmissions in unicast communication.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that NC offers exciting benefits in terms of throughput, reliability, cost, and delay in wireless networks [15][16][17][18]. Specifically, the reliability gain of NC was studied recently in [7,19,20]. The work in [19] confirmed that NC could increase the reliability by reducing the number of transmissions in unicast communication.…”
Section: Related Workmentioning
confidence: 99%
“…After receiving the required number of encoded packets, a receiver can decode out the original packets. Recent work [7] shows that NC can improve reliability by reducing the number of packet retransmissions in wireless lossy networks.…”
Section: Introductionmentioning
confidence: 99%
“…For throughput, network coding technique can take advantages of bottleneck effect of data at the intermediate node in wireless communication to improve the system throughput [3]. Ghaderi et al [4] have shown that there are reliability benefits by applying network coding technique in their system. Li et al [5] show that the maximum achievable rate can be achieved by linearly combining input packets at an intermediate node.…”
Section: Introductionmentioning
confidence: 99%
“…The potential advantages of network coding over routing include the enhancement in network throughput [4][5][6], reliability [7][8][9], energy efficiency [10,11], security [12] and others [13][14][15][16]. Due to these promising benefits, network coding has found a wide range of applications in ad hoc networks [17][18][19], wireless mesh networks [6,[20][21][22][23], peer-to-peer communication systems [24][25][26] and distributed data storage [27].…”
Section: Chapter 1 Introduction 11 Motivation and Objectivesmentioning
confidence: 99%
“…One commonly used field size for RLNC is 28 . Here, a small field size is used for illustration purposes.…”
mentioning
confidence: 99%